Heterogeneously‐Catalyzed Hydrogenation of Carbon Dioxide to Methane using RuNi Bimetallic Catalysts. Issue 1 (12th November 2014) - Lange, Felix; Armbruster, Udo; Martin, Andreas
Abstract One facet of the future energy supply can be covered by the use of synthetic natural gas (SNG) obtained from carbon dioxide and hydrogen using excess solar or wind energy to power water electrolysis. In this article, zirconia supported RuNi bimetallic catalysts were evaluated for this reaction at 300–400 °C, 10 bar, and space velocities up to 36 000 h−1. In general, the reaction is close to the equilibrium; CO2 conversion is complete, and SNG selectivity is close to 100 %. The studies have shown that Ru can be partially substituted by Ni to achieve similar product performance. Bimetallic catalysts with low loadings show the formation of alloys but higher loadings lead to segregation and agglomeration of Ni particles. The SNG productivity (at 36 000 h−1) reached on the best catalysts approximately 70 kg kgRu−1 h−1 and 40 kg kgNi−1 h−1, respectively. Thus, a SNG space‐time‐yield of approximately 50–100 kg kgmetal−1 h−1 (70–140 N m3 h−1) can be obtained to this point.